2019
DOI: 10.1016/j.envpol.2018.10.130
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of the benzotriazole ultraviolet stabilizers UV-234 and UV-320 in early-staged zebrafish (Danio rerio)

Abstract: Among the benzotriazole ultraviolet stabilizers (BUVSs), UV-234 and UV-320 are frequently detected in aquatic ecosystem. Despite the fact that these chemicals are present in low ng/L levels in surface water, they show high bio-accumulation potential and pose exposure risks to aquatic organisms. However, there are limited toxicological data available in fish. In this study, zebrafish embryos were exposed to 0.01, 0.1 and 1 mM UV-234 or UV-320 for up to 6 days. Developmental toxicity as well as effects on mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(21 citation statements)
references
References 65 publications
2
19
0
Order By: Relevance
“…24 It has also been reported that BUVSs can perturb mitochondrial bioenergetics, embryonic development, locomotor activity, and the thyroid system of zebrafish. 24,64 The accumulation in the ovaries further highlights the importance of understanding the effects of exposure to these industrial chemicals on the early-life stage of fish.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…24 It has also been reported that BUVSs can perturb mitochondrial bioenergetics, embryonic development, locomotor activity, and the thyroid system of zebrafish. 24,64 The accumulation in the ovaries further highlights the importance of understanding the effects of exposure to these industrial chemicals on the early-life stage of fish.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…The accumulated BUVSs in the ovaries can be transferred to eggs and induce adverse effects on offspring. Previous studies indicated that exposure of zebrafish to BUVSs led to increased hatching time of embryos 64 and decreased heart rates of the larval fish. 24 It has also been reported that BUVSs can perturb mitochondrial bioenergetics, embryonic development, locomotor activity, and the thyroid system of zebrafish.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Because of their extensive and increasing use, a large variety of UV filters are leaching into the environment, gaining more and more attention regarding their risks to the environment and human health. , Current concerns over UV filters are primarily focused on the benzophenone- and benzotriazole-type chemicals . These two types of UV filters have been recorded worldwide to occur in various environmental and biological matrices, including air, water, sediment, dust, sludge, bird eggs, and human urine. , Furthermore, multiple toxic effects of these UV filters have also been widely demonstrated, including endocrine disruption, neurotoxicity, reproductive toxicity, and developmental toxicity. …”
Section: Introductionmentioning
confidence: 99%
“…Such widespread use leads to detectable concentrations of BT-UVs in environmental matrices, which have been reported for surface water ( Lu et al., 2016 ), sea water ( Montesdeoca-Esponda et al., 2020 ), sediment ( Cantwell et al., 2015 ), biota ( Lu et al., 2019 ), wastewater ( Song et al., 2014 ) and plastic debris ( Rani et al., 2017 ). The toxic and bio-accumulative properties of BT-UVs are well documented ( Kim et al., 2011 ; Liang et al., 2019 ); and as a result, some BT-UVs have been classified under the European Registration, Evaluation, Authorization and Restriction of Chemicals (REACH) regulation as substances of very high concern (European Chemicals Agency (ECHA), 2014 ).…”
Section: Introductionmentioning
confidence: 99%